2011
DOI: 10.1158/1078-0432.ccr-11-0649
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of MUC-1/CEA/TRICOM Poxviral-Based Vaccine in Patients with Metastatic Breast and Ovarian Cancer

Abstract: Purpose PANVAC is a recombinant poxviral vaccine that contains transgenes for MUC-1, CEA and 3 T-cell costimulatory molecules. This study was conducted to obtain preliminary evidence of clinical response in metastatic breast and ovarian cancer patients. Experimental design Twenty-six patients were enrolled and given monthly vaccinations. Clinical and immune outcomes were evaluated. Results These patients were heavily pretreated, with 21 of 26 patients having ≥ 3 prior chemotherapy regimens. Side effects we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 38 publications
1
69
0
Order By: Relevance
“…Together, these data suggest that breast cancer vaccines may have the highest efficacy when combined with other therapeutic modalities. Consistent with earlier findings showing an inverse correlation between prior chemotherapy and the efficacy of vaccine treatment (von Mehren et al, 2000;, a recently reported pilot study of a MUC-1/CEA/TRICOM poxviral-based vaccine showed that only 1 of 12 patients with breast cancer had an objective complete response, whereas all the others had rapid progression of disease (Mohebtash et al, 2011). The only responder was a patient who had minimal disease and was not as heavily pretreated as the others, suggesting that breast cancer vaccine monotherapy in patients with heavy tumor burdens or extensive prior treatment with chemotherapy is not likely to produce a significant clinical benefit.…”
Section: Therapeutic Vaccinessupporting
confidence: 89%
“…Together, these data suggest that breast cancer vaccines may have the highest efficacy when combined with other therapeutic modalities. Consistent with earlier findings showing an inverse correlation between prior chemotherapy and the efficacy of vaccine treatment (von Mehren et al, 2000;, a recently reported pilot study of a MUC-1/CEA/TRICOM poxviral-based vaccine showed that only 1 of 12 patients with breast cancer had an objective complete response, whereas all the others had rapid progression of disease (Mohebtash et al, 2011). The only responder was a patient who had minimal disease and was not as heavily pretreated as the others, suggesting that breast cancer vaccine monotherapy in patients with heavy tumor burdens or extensive prior treatment with chemotherapy is not likely to produce a significant clinical benefit.…”
Section: Therapeutic Vaccinessupporting
confidence: 89%
“…In breast cancer, a phase II study is conducted in the neoadjuvant setting by the Austrian Breast and Colorectal Cancer Study Group (ABCSG-34 trial). Two other tumor vaccines targeting MUC1 have been developed that are currently tested in clinical trials [27,28]. Antibodies targeting MUC1 have had limited success so far, maybe due to the presence of circulating MUC1 in patient serum.…”
Section: Discussionmentioning
confidence: 99%
“…PANVAC TM (Therion Biologics Corp., Cambridge, MA, USA) targets both MUC-1 and CEA; it uses viral vectors to deliver the antigen together with 3 human T-cell costimulatory molecules [16]. In early clinical trials in heavily pretreated patients, the vaccine demonstrated some clinical activity, including a complete response [17,18].…”
Section: Anti Muc-1 Vaccinesmentioning
confidence: 99%